POSISI KEBERLANJUTAN INDONESIA DALAM PENCAPAIAN SDGs PANGAN DAN PERTANIAN : ANALISIS RAP-SDGs DI ASIA TENGGARA - Tambunan, Varingan Prianando (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The Sustainable Development Goals (SDGs) agenda emphasizes the integration of economic, social, and environmental dimensions in realizing a sustainable food and agricultural system. This study analyzes Indonesia's sustainability position compared to eleven Southeast Asian countries using the RAP-SDGs method based on Multidimensional Scaling (MDS). Secondary data from the FAO SDGs Database for the period 2019–2024 was used to compile a sustainability index, identify leverage indicators through leverage analysis, and evaluate outcome uncertainties through 100 iterations of Monte Carlo simulations. The results showed significant differences between countries, where only Indonesia, Thailand, Timor Leste, and Viet Nam reached the "moderately sustainable" category. Indonesia occupies the highest position overall, supported by the strongest ecological performance, while the economic dimension is the main weakness of the region. Leverage analysis revealed that the Agriculture Orientation Index is the largest lever in the economic dimension, access to land and resources is the main lever of the social dimension, and IUU fishing and environmental status conditions are the main determinants of the ecological dimension. Monte Carlo confirmed the consistency of the pattern, with Indonesia showing high resilience to the ecological dimension. These findings underscore the need to improve agricultural budget orientation, protect access to resources, and strengthen environmental policies to accelerate the achievement of SDGs 2030 in Indonesia and the region.